Developments in hot-filament metal oxide deposition (HFMOD) - Durrant, Steven F. [UNESP]; Trasferetti, Benedito C.; Scanninio, Jair; Davanzo, Celso U.; Rouxinol, Francisco P. M.; Gelamo, Rogerio V.; de Moraes, Mario A. Bica (Elsevier B.V. Sa, 2008)
Hot-filament metal oxide deposition (HFMOD) is a variant of conventional hot-filament chemical vapor deposition (HFCVD) recently developed in our laboratory and successfully used to obtain high-quality, uniform films of MOx WOx and VOx. The method employs the controlled oxidation of a filament of a transition metal heated to 1000 degrees C or more in a rarefied oxygen atmosphere (typically, of about 1 Pa). Metal oxide vapor formed on the surface of the filament is transported a few centimetres to deposit on a suitable substrate. Key system parameters include the choice of filament material and diameter, the applied current and the partial pressures of oxygen in the chamber. Relatively high film deposition rates, such as 31 nm min(-1) for MoOx, are obtained. The film stoichiometry depends on the exact deposition conditions. MoOx films, for example, present a mixture of MoO2 and MoO3 phases, as revealed by XPS. As determined by Li+ intercalation using an electrochemical cell, these films also show a colouration efficiency of 19.5 cm(2) C-1 at a wavelength of 700 nm. MOx and WOx films are promising in applications involving electrochromism and characteristics of their colouring/bleaching cycles are presented. The chemical composition and structure of VOx films examined using IRRAS (infrared reflection-absorption spectroscopy), RBS (Rutherford backscattering spectrometry) and XPS (X-ray photoelectron spectrometry) are also presented. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: hot-wire CVD; electrochromism; tungsten oxide; molybdenum oxide; vanadium oxide; thin films